Infusion devices (ANSI/AAMI, 1993)
This standard establishes minimum labeling, safety, performance, and testing requirement for mechanical and electromechanical infusion devices that have a pumping or gravity-feed controlling function, that deliver fluid from either a separate or a self-contained source, and that are intended for use with parenteral fluids for such purposes as parenteral nutrition and administration of drugs and routine fluids.